Parents perceptions of HIV counselling and testing in schools: ethical, legal and social implications - Gwandure, Ruth (My University, 2014)
Given the high prevalence of HIV and AIDS in South Africa, particularly among the 12-25 year age group, the study set out to understand the perceptions of parents regarding the proposed school-based HIV Counselling and Testing (HCT) campaign planned by the Department of Health in collaboration with the Department of Education. This campaign is aimed at encouraging teenagers to get tested and to know their HIV status in the hope that such knowledge will reduce the number of new infections. The target market of the HCT campaign includes high schools because they have a significant number of adolescents and young adults who could benefit from HCT campaign (SANAC, 2010:11). The research looked at the ethical, legal and social implications of the HCT campaign in schools as perceived by parents. Semi-structured interviews were conducted with a sample of 20 households. Among the main findings was that parents were generally in favour of the HCT campaign but believed that participation in the programme should be voluntary. They anticipated that the HCT programme could potentially affect children’s emotional well-being, particularly if ethico-legal issues of consent and confidentiality were violated and social issues of stigma and discrimination were not handled sensitively. They emphasised that the campaign needed to consider children’s vulnerability and should seek to protect them in the process. Findings are discussed in terms of their implications for promoting bioethical principles in implementing the HCT campaign.
Keywords: HIV--diagnosis; Counseling; Ethics, Medical